Імперативи глобального мережевого суспільства - Онопрієнко, В.І. (№10, 2007)
The situation that is new for national scientific systems and connected with global internet development which accentuates the problem of intellectual product inclusion into world scientific space is evaluated. The real state and prospects of Ukrainian science in the frame of its participation in the world business connections of the global net community are investigated.